The Relationship between Knowledge and Free Sexual Behavior among Adolescents - Ainul Maghfiroh (Global Health Science Group, 2025)
Adolescent knowledge about reproductive health and the risks of promiscuous sexual behavior is one of the important factors in determining their sexual behavior. Adolescents with less knowledge about the risks of promiscuous sex tend to have a higher tendency to engage in risky sexual behavior compared to adolescents with good knowledge. The purpose of this study was to determine the relationship between knowledge and promiscuous sexual behavior in adolescents. The research method is a quantitative study with a cross-sectional approach, statistical tests were analyzed using the Chi Square statistical test. The research instrument used a questionnaire on knowledge and promiscuous sexual behavior that had been tested for validity and reliability, a population of 4940 respondents with a purposive sampling technique, a sample of 98 adolescents aged 15-19 years. The results of the study showed a relationship between knowledge and promiscuous sexual behavior in adolescents with a p value of 0.021 and an OR value of 2.71, which means that poor knowledge increases the risk of bad promiscuous sexual behavior by 2.71 times than good knowledge. Conclusion: there is a relationship between knowledge and promiscuous sexual behavior.